Understanding higher-order constructs of leadership and communication in EMS clinical judgment - Mihaiela R. Gugiu; Jennifer Cotto; Yin Burgess; Jonathan Powell; Ashish R. Panchal (BMC Medical Education)
Abstract Background For emergency medical services (EMS) clinicians, clinical judgment is a higher-order construct that encompasses the initial thought process (clinical reasoning) that assists clinicians in reaching conclusions (clinical decision making). Current theoretical frameworks of clinical judgment contain other higher order constructs (e.g., leadership, communication) which may play a significant role in delivery of care. It is unknown whether this definition of clinical judgment includes additional higher order constructs of leadership and communication. The goal of this evaluation was to determine whether leadership and communication overlap and are subsumed under the larger construct of clinical judgment. Methods Focus groups of experts in prehospital paramedic and advanced emergency medical technician levels of certification were recruited to generate tasks and their associated knowledge, skills, and abilities (KSAs) in for the domains of clinical judgment, communication, and leadership. These tasks and KSAs were then evaluated for commonality between the domains to evaluate whether communication and leadership are incorporated within clinical judgment. Results Task-KSA matrices were generated by focus groups for each domain and evaluated by certification level. There were no differences by certification level in the tasks-KSA matrices for the domains. A total of 77 tasks were identified, comprised of 392 KSAs across three domains (9 sub-domains). An analysis of commonality of tasks between the domains of communication and leadership with clinical judgment demonstrated that 61% of communication tasks were similar to the identified clinical judgment tasks. Similarly, in leadership, clinical judgment had a total of 79% commonality overall. Conclusion Clinical judgment was found to be a higher order construct that overlaps with and incorporates the domains of leadership and communication in the theoretical framework of EMS clinical judgment. This study provides validity evidence for the proposed clinical judgment theoretical framework. Future work should focus on pilot evaluations in simulated settings for building additional construct validity.